Heterotopic peritoneal echinococcosis of splenic origin in children - Anavitarte, Eduardo; Arruti, César; Torres, David (Cirugía del Uruguay, 1973)
In this paper we present one case of primitive heterotopic peritoneal echinococcosis of splenic origin in a 3-year-old child, for the purpose of íts inclusion in case material. The mentioned complicatíon is rare at this age, since this pathological process, rare in itself, is generally seen in cysts which have reached a Jarge volume.